Corona Fictions as Cultural Indicators of Social Cohesion and Resilience in the Wake of the Covid-19 Pandemic - Obermayr, Julia; Völkl, Yvonne (Momentum Quarterly, 2022)
Since the beginning of the Covid-19 pandemic, many Europeans have turned to preexisting written and audiovisual pandemic fictions and as a coping strategy. Two years into the crisis, on a cultural level, numerous European countries have since actively produced their own Corona Fictions offering narratives that deal with the current pandemic. On a societal level, these narratives early on hinted at potential ruptures in social cohesion. Cultural productions commonly function as an enabler of social cohesion, fostering mutual understanding and a feeling of togetherness, particularly when considering the participatory nature of narratives on the internet or in literary anthologies. Originating in a research project of a much larger scope, this article explores the following questions in two francophone cultural productions of the Covid-19 pandemic. In which areas is social cohesion shaken or fractured? How is social cohesion experienced, processed, and expressed? Does the reception of Corona Fictions function as a coping strategy? How do gender issues/inequalities aggravated by the pandemic translate into the representation of female characters in Corona Fictions?